Asymmetries on Closed End Country Funds Premium and Monetary Policy Announcements: An Approach Trough the Perspective of Foreign Countries - Stylianos X. Koufadakis (SPOUDAI - Journal of Economics and Business, 2015)
In this paper we examine how monetary announcements can explain US country funds premiums in international markets, taking into account monetary asymmetries relating to information news and directional actions of monetary policy. The monetary determinants which we have used to explore the closed-end fund puzzle emanate from the announcements of official rates of the countries of origin of NAVs. Our conclusions which reflect the investor sentiment as it varies in developing and emerged markets are supported by appropriate monetary assumptions concerning the role of monetary announcements. We find out that neither the expected nor the unexpected component of the monetary rate retains a dominant role in interpreting the fund premiums. In the case of developing funds the age has a negative influence on premium, while in developed funds the main fund's benchmark index has a positive correlation with the fund premium. Moreover, the foreign exchange rate plays a significantly negative role in the CEFCs of developed countries and a positive role in those of developing markets. But the proxy for the US equity market seems to positively influence the whole range of funds. By examining the possible asymmetries we can see that premiums are negatively affected by unfavorable monetary news. We have also considered the case in which asymmetries on the funds premiums are based on the direction of the monetary policy, as shaped by the decisions of central banks in foreign countries.
Keywords: G12; G23; E52; 330; Closed-end country funds; monetary policy; international markets; asymmetric information